Dealing With Death Taboo: Discussion of Do-Not-Resuscitate Directives With Chinese Patients With Noncancer Life-Limiting Illnesses. (September 2019) - Cheng, Hon-Wai Benjamin; Shek, Pui-Shan Karen; Man, Ching-Wah; Chan, Oi-Man; Chan, Chun-Hung; Lai, Kit-Man; Cheng, Suk-Ching; Fung, Koon-Sim; Lui, WK; Lam, Carman; Ng, Yuen-Kwan; Wong, Wan-To; et al.
Background: Noncancer patients with life-limiting diseases often receive more intensive level of care in their final days of life, with more cardiopulmonary resuscitation performed and less do-not-resuscitate (DNR) orders in place. Nevertheless, death is still often a taboo across Chinese culture, and ethnic disparities could negatively affect DNR directives completion rates. Objectives: We aim to explore whether Chinese noncancer patients are willing to sign their own DNR directives in a palliative specialist clinic, under a multidisciplinary team approach Design: Retrospective chart review of all noncancer patients with life-limiting diseases referred to palliative specialist clinic at a tertiary hospital in Hong Kong over a 4-year period. Results: Over the study period, a total of 566 noncancer patients were seen, 119 of them completed their own DNR directives. Patients had a mean age of 74.9. Top 3 diagnoses were chronic renal failure (37%), congestive heart failure (16%), and motor neuron disease (11%). Forty-two percent of patients signed their DNR directives at first clinic attendance. Most Chinese patients (76.5%) invited family caregivers at DNR decision-making, especially for female gender (84.4% vs 69.1%; P = .047) and older (age >75) age group (86.2% vs 66.7%; P = .012). Of the 40 deceased patients, median time from signed directives to death was 5 months. Vast majority (95%) had their DNR directives being honored. Conclusion: Health-care workers should be sensitive toward the cultural influence during advance care planning. Role of family for ethnic Chinese remains crucial and professionals should respect this family oriented decision-making.